Strategi Komunikasi Pemasaran Dinas Pariwisata Daerah Istimewa Yogyakarta Melalui Konten Instagram Pasca Pandemi Covid-19 - Permono, Mohammad Shidiq (AGUNA: Jurnal Ilmu Komunikasi, 2023)
Tourism marketing communication is an important component that must be owned by every tourism industry in carrying out activities by providing detailed and structured services. Effective tourism marketing will provide intermediaries and bridges with business people and potential customers, both directly and through intermediary markets. In processing tourism marketing, an efficient plan is needed to increase success and reduce the risk of failure. This study aims to determine marketing communication strategies and processing post-Covid-19 tourism communications through Instagram social media content to attract local and foreign tourists who will visit Yogyakarta. The results of the study show that the DIY Tourism Office creates various kinds of content which contain various tourist destinations in Yogyakarta and uploads some other information about DIY tourism which is one of the strategies to revive interest in tourism which was previously halted due to the Covid-19 pandemic and increase returns. marketing percentage figures in Yogyakarta. The theory used in this study uses the marketing process theory put forward by Lamb, Hair, and McDaniel (2001) and the Marketing Mix Theory. The research method this time uses a qualitative descriptive, observation and documentation study. By collecting data using the Miles and Huberman models with data collection, data reduction, and data presentation, data is obtained by conducting in-depth reports or conducting in-depth interviews with sources from the DIY Tourism Office.